Shape Accuracy in Single Point Incremental Forming of Conical Frustums from Titanium CP2 Sheets - Szpunar, Marcin; Balcerzak, Maciej; Żaba, Krzysztof (Advances in Mechanical and Materials Engineering, 2022)
This paper presents frustum cone drawpiece analysis made of titanium CP2 sheet by a single incremental sheet forming. Central composite design has been adopted to carry out an experiment containing 20 runs, then multi-criteria parameter optimization has been done. Optimal parameters have been validated and responses deviations do not exceed 4% compared to created models. For the drawpiece formed with optimal parameters, AGRUS optical measurement and X-ray tomography has been applied to check the obtained of the part wall thickness and general deviations compared to the CAD model. The wall angle discrepancy of the cone generatrix has also been analyzed. No gaps or ruptures have been confirmed by X-ray. The blank rolling direction has a significant effect on the drawpiece deviations. The measurement results showed deviations of the drawpiece wall angle +0.27°/- 0.06°, sheet thickness on the cone +0.012/-0.04 mm and +0.151/-0.096 mm from the reference CAD geometry.